Pengaruh Koefisien Nk Terhadap Kuat Geser Tanah Lunak Gedebage Berdasarkan Uji CPTu - Desiani, Asriwiyanti; Wiyono, Daud R.; Pramono, Adrian (Universitas Kristen Maranatha, 2024)
Cone Penetration Test field instrument, also commonly refered to as sondir, has been commonly used in Indonesia. However, the usage of Cone Penetration Test in combination with pore water measurement (CPTu) is not yet used widely, which is why this research is conducted in situ by using CPTu instrument. In situ testing has a few advantages, such as:soil parameters are obtained under actual stress conditions, continous data can be obtained along the depth of soil, and it overcomes sampling problems or sample interferences. Location of this research is in Gedebage area of Bandung which currently undergoes major development. Soil in the area are soft soils which commonly have low shear strength. Soft clay shear strength (Su) can be determined by the ratio of net cone resistance and conus factor (Nkt). Further research on Nkt coefficient on soft soil shear strength evaluation based on CPTu test results are going to be verified by using laboratory testing. The research shows that Nkt coefficient which are suitable for Gedebage area ranges from 13 - 15. Range of shear strength parameter based on the laboratory test and in situ CPTu test calculations are as the following: depth of 0-10 m Su >25 kPa, depth of 10 - 25m Su is around 10 kPa, and depth of 25 - 31m Su > 100 kPa.